Biodiversity of Klebsormidium (Streptophyta) from alpine biological soil crusts (Alps, Tyrol, Austria, and Italy). Issue 4 (14th July 2015) - Mikhailyuk, Tatiana; Glaser, Karin; Holzinger, Andreas; Karsten, Ulf; Gabrielson, P.
<x xml:space="preserve">Abstract</x> Forty Klebsormidium strains isolated from soil crusts of mountain regions (Alps, 600–3, 000 m elevation) were analyzed. The molecular phylogeny (internal transcribed spacer rDNA sequences) showed that these strains belong to clades B/C, D, E, and F. Seven main (K. flaccidum, K. elegans, K. crenulatum, K. dissectum, K. nitens, K. subtile, and K. fluitans) and four transitional morphotypes (K. cf. flaccidum, K. cf. nitens, K. cf. subtile, and K. cf. fluitans) were identified. Most strains belong to clade E, which includes isolates that prefer humid conditions. One representative of the xerophytic lineage (clade F) as well as few isolates characteristic of temperate conditions (clades B/C, D) were found. Most strains of clade E were isolated from low/middle elevations (<1, 800 m above sea level; a.s.l.) in the pine‐forest zone. Strains of clades B/C, D, and F occurred sporadically at higher elevations (1, 548–2, 843 m a.s.l.), mostly under xerophytic conditions of alpine meadows. Comparison of the alpine Klebsormidium assemblage with data from other biogeographic regions indicated similarity with soil crusts/biofilms from terrestrial habitats in mixed forest in Western Europe, North America, and Asia, as well as walls of buildings in Western European cities. The alpine assemblage differed substantially from crusts from granite outcrops and sand dunes in Eastern Europe (Ukraine), and fundamentally from soil crusts in South African drylands. Epitypification of the known species K. flaccidum, K. crenulatum, K. subtile, K. nitens, K. dissectum, K. fluitans, K. mucosum, and K. elegans is proposed to establish taxonomic names and type material as an aid for practical studies on these algae, as well as for unambiguous identification of alpine strains. New combination Klebsormidium subtile (Kützing) Mikhailyuk, Glaser, Holzinger et Karsten comb. nov. is made.